2006
DOI: 10.1029/2006gc001398
|View full text |Cite
|
Sign up to set email alerts
|

Mantle transition zone structure and upper mantle S velocity variations beneath Ethiopia: Evidence for a broad, deep‐seated thermal anomaly

Abstract: [1] Ethiopia has been subjected to widespread Cenozoic volcanism, rifting, and uplift associated with the Afar hot spot. The hot spot tectonism has been attributed to one or more thermal upwellings in the mantle, for example, starting thermal plumes and superplumes. We investigate the origin of the hot spot by imaging the S wave velocity structure of the upper mantle beneath Ethiopia using travel time tomography and by examining relief on transition zone discontinuities using receiver function stacks. The tomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
80
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(94 citation statements)
references
References 51 publications
(86 reference statements)
13
80
1
Order By: Relevance
“…An elevated temperature is coherent with the geodynamic context and tomographic results [e.g., Benoit et al, 2006].…”
Section: The 410 Discontinuitymentioning
confidence: 97%
See 3 more Smart Citations
“…An elevated temperature is coherent with the geodynamic context and tomographic results [e.g., Benoit et al, 2006].…”
Section: The 410 Discontinuitymentioning
confidence: 97%
“…Tauzin et al [2008] observed both discontinuities to be depressed by 30-50 km, most likely caused by the use of a velocity model without slow upper mantle anomalies. A study using regional deployments [Benoit et al, 2006] found the MTZ beneath Ethiopia to be complex and reported no conclusive evidence for the '410' with P-to-S converted-waves, whereas the '660' is mapped with considerable relief (625-675 km).…”
Section: Geodynamic Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…1) is matter of an ongoing debate. Topographic elevation and gravity field (e.g., Ebinger and Hayward 1996;Woldetinsae and Götze 2005) and seismic velocity anomalies in the mantle (e.g., Ritsema and Allen 2003;Benoit et al 2006;Sebai et al 2006) indicate major thermal anomalies in the mantle, which occur according to the seismic velocities in the asthenosphere and in the deep mantle. The anomalies in the deep mantle are ascribed to mantle plume activity, but the relations between deep and shallow mantle's anomalies are still unresolved (e.g., Ritsema and Allen 2003;Benoit et al 2006).…”
Section: Introductionmentioning
confidence: 99%